Tooth-size Discrepancy - An important diagnosis tool to measure the outcome of Orthodontic Treatment Completion: A Review - Hasan, Md. Nazmul; Chowdhury, Shirin Sultana; Khan, Md. Ali Afzal; Taleb, Asma; Abid, Mohammad Mainul Hasan (Bangladesh Journal of Dental Research & Education, 2013)
Bangladesh Journal of Dental Research & Education, Vol. 01, No. 01, January 2011, Page 27-29 DOI: http://dx.doi.org/10.3329/bjdre.v1i1.15799